Longitudinal Profiles of Dietary and Microbial Metabolites in Formula- and Breastfed Infants - Sillner, Nina; Walker, Alesia; Lucio, Marianna; Maier, Tanja V.; Bazanella, Monika; Rychlik, Michael; Haller, Dirk; Schmitt-Kopplin, Philippe (Frontiers in Molecular Biosciences, 2021)
The early-life metabolome of the intestinal tract is dynamically influenced by colonization of gut microbiota which in turn is affected by nutrition, i.e. breast milk or formula. A detailed examination of fecal metabolites was performed to investigate the effect of probiotics in formula compared to control formula and breast milk within the first months of life in healthy neonates. A broad metabolomics approach was conceptualized to describe fecal polar and semi-polar metabolites affected by feeding type within the first year of life. Fecal metabolomes were clearly distinct between formula- and breastfed infants, mainly originating from diet and microbial metabolism. Unsaturated fatty acids and human milk oligosaccharides were increased in breastfed, whereas Maillard products were found in feces of formula-fed children. Altered microbial metabolism was represented by bile acids and aromatic amino acid metabolites. Elevated levels of sulfated bile acids were detected in stool samples of breastfed infants, whereas secondary bile acids were increased in formula-fed infants. Microbial co-metabolism was supported by significant correlation between chenodeoxycholic or lithocholic acid and members of Clostridia. Fecal metabolites showed strong inter- and intra-individual behavior with features uniquely present in certain infants and at specific time points. Nevertheless, metabolite profiles converged at the end of the first year, coinciding with solid food introduction. Trial registration: DRKS, DRKS00003660. Registered 03.08.2012; https://www.drks.de/